Clinical and ultrasonographic screening for carpal tunnel syndrome in hemodialysis patients - Samar Tharwat; Mohammed Kamal Nassar (The Korean Society of Nephrology, 2020)
Background : Carpal tunnel syndrome (CTS) is one of the most common complications among hemodialysis (HD) patients. This study aimed to assess the prevalence of CTS in HD patients using clinical and noninvasive ultrasound (US) criteria. Methods : A cross-sectional, observational study was conducted on 94 HD patients to evaluate CTS manifestations and demographic, clinical, and laboratory data. The median nerve (MN) cross sectional area (CSA) (MN-CSA) was estimated by US examination at the pisiform and hamate levels. Both hands were evaluated, and the higher MN-CSA was considered. Results : Neuropathic pain and nocturnal numbness at MN distribution were present in 40.4% and 18.1%, respectively, while Tinel's test was positive in 25.5% of patients. A MN-CSA ≥ 11.5 mm2 identified the probability of CTS with 63% sensitivity and 80% specificity. Patients with CTS had higher serum calcium (P = 0.02) and lower parathyroid hormone (PTH) (P = 0.02). CTS was frequently developed on the same side of an arteriovenous fistula. The MN-CSA had positive correlations with age, serum phosphorus, and visual analogue scale (VAS) score (P = 0.01, 0.01, and 0.03 respectively) and a negative correlation with PTH level (P = 0.007). Serum phosphorus level (P = 0.015) and VAS (P = 0.04) were the significant predictors of MN-CSA. Conclusion : CTS appears to frequently occur in HD patients. US examination may be helpful in detection of CTS and can be an alternative to electrodiagnostic studies in HD patients.